Critical Constants Correlation from van der Waals Equation (2019)
The cubic van der Waals equation of state at the critical condition is reduced to a linear function (Vc vs. Tc /Pc coordinates) with one adjustable parameter. It is shown that at the critical point the relation Vc = 3Vo must not hold as van der Waals suggested, but the attractive constant α = Pc Vc2 remains. Selected values of Tc, Pc, Vc compiled by Ihmels where focused on testing the quality of several empirical equations relating critical conditions. It is shown that the obtained critical constants correlation is a general form of the empirical expressions proposed by Young, Meissner, Bird, Grigoras and Ihmels. From the resulting correlation function, a function for the critical compressibility is proposed. The critical volume Vc and the ratio Tc /Pc have been expressed in group contributions.